Perancangan Sistem Informasi Inventori Koperasi Sekolah Berbasis Website Dengan Metode RAD - Muhamad Syaid Husein Nasrullah; Farizi Ilham; Nurlayla Fitri; Raya Astri Rinzani (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
The school cooperative of SMP Negeri 17 Tangerang Selatan still records inventory data manually and partly uses Microsoft Excel. This practice causes data retrieval to take longer, stock monitoring to be less accurate, and incoming and outgoing goods reports to be prepared manually. This study aims to design a web based inventory information system using the Rapid Application Development (RAD) method. Data were collected through observation, interviews with cooperative staff, and literature review. RAD stages were applied through requirement planning, user design, construction, and initial cutover. The proposed system includes item data management, incoming goods records, outgoing goods records, stock monitoring, inventory reports, and user access management. The design results indicate that a web-based system can help the cooperative manage inventory data in a more organized, faster, and centralized manner, supporting the daily operations of the school cooperative.